Faktor Yang Berhubungan Dengan Tindakan Tidak Aman Pada Buruh Di Pelabuhan Nusantara Parepare (Window of Public Health Journal, 2025)
A work accident is an incident that occurs suddenly, unintentionally, and can result in the loss of life and property. An unsafe act, or an unsafe action, is a behavior that can pose a risk to the worker or other workers in the workplace, resulting in an incident due to various factors. This study applies a quantitative method using a cross-sectional study research design. This study's results show that knowledge and training variables are significantly related to unsafe acts committed by stevedoring workers at the Nusantara Parepare port. In contrast, the variables of work period and supervision do not have a significant relationship with unsafe acts in stevedoring workers (TKBM) at the Nusantara Parepare port. Workers must carry out their work while still following the safety procedures that have been implemented. The importance of increasing worker knowledge and training regarding Occupational Health and Safety is so that workers can protect themselves and others while doing their work. Workers should rest when they feel tired and pay more attention to a healthy lifestyle.